2005
DOI: 10.1682/jrrd.2005.01.0025
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-life predictors for caregivers at 1 and 6 months poststroke: Results of path analyses

Abstract: In this study, we used path analyses to test a theoretical model of influences on quality of life (QOL) for stroke caregivers at 1 and 6 months poststroke. We examined data from two points in time to determine the influence of stroke survivor and caregiver characteristics on QOL for stroke caregivers. Stroke survivor and caregiver characteristics had some direct influence on QOL outcomes for stroke caregivers at both 1 and 6 months poststroke. However, the most influential factor at both time points on each QO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 49 publications
3
39
0
3
Order By: Relevance
“…Findings by Coe et al are usually in agreement with findings from general caregiving research and caregiving research using salutogenic theory conducted during the two decades that have elapsed since their work. In line with later findings, the experience of burden seems related to caregiver characteristics (e.g., SOC) and caregivers' efforts to prevent problems more than to care recipients' functional level and care needs [45].…”
Section: Salutogenesis and Caregiving Researchsupporting
confidence: 82%
See 2 more Smart Citations
“…Findings by Coe et al are usually in agreement with findings from general caregiving research and caregiving research using salutogenic theory conducted during the two decades that have elapsed since their work. In line with later findings, the experience of burden seems related to caregiver characteristics (e.g., SOC) and caregivers' efforts to prevent problems more than to care recipients' functional level and care needs [45].…”
Section: Salutogenesis and Caregiving Researchsupporting
confidence: 82%
“…Research in this field evolved to encompass a broader focus on psychosocial aspects such as wellbeing [35], occasionally in new ways and settings [36]. Studies combining both positive and negative aspects began to appear [37][38][39] and the complex existential dimension of caregiving came into focus through concepts such as meaning [40][41][42][43] and quality of life [36,44,45].…”
Section: Caregiving By Informal Caregiversmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, some experimental studies have been conducted [36][37][38] ; however, a study of caregivers has not yet been reported. Van Puymbroeck et al 39) studied QOL predictors in caregivers of stroke patients, and reported that SOC is the most influential factor in their QOL, and that such caregivers who can mobilize their coping resources effectively experience fewer burdens in QOL and fewer symptoms of depression. Our results show that the SOC of caregivers is significantly higher than that of the general population within the same age group.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lazurus' coping theory, if perceived demands exceed perceived resources, decreased quality of life may be one of the consequences of poor coping (Kim & Given, 2008;Lazarus, 1993). If on the other hand caregivers can mobilize their resources to handle the stress of caregiving, quality of life may not suffer (Van Puymbroeck & Rittman, 2005). Thus, quality of life is an outcome that results from a variety of internal and external factors (e.g.…”
mentioning
confidence: 99%